Analysis Of Down Passing Techniques In Volleyball Games For Extracurricular Participants At SMP Negeri 19 Bengkulu City - F. Kurniawan; Martiani Martiani; Algifari Syarif (Sinar Sport Journal, 2021)
This study aims to analyze the technique of passing down on volleyball extracurricular participants at SMP Negeri 19 Bengkulu City. The method used in this research is a survey method with data collection techniques using observation sheets, with the type of descriptive research. The population in this study were volleyball extracurricular participants at SMP Negeri 19 Bengkulu City. The sampling technique uses total sampling, namely the technique of determining the sample by taking the entire population. Based on this, the sample in this study amounted to 12 participants. Data analysis used quantitative descriptive as outlined in the form of a percentage. The results showed that the analysis of the technique of passing down on volleyball extracurricular participants at SMP Negeri 19 Bengkulu City was in the "very low" category of 0% (0 participants), "low" of % (0 participants), "medium" of 25% (3 participants), “high” at 75% (9 participants), and “very high” at 0% (0 participants).